Age and orbital forcing in the upper Silurian Cellon section (Carnic Alps, Austria) uncovered using the WaverideR R package - Arts, Michiel; Corradini, Carlo; Pondrelli, Monica; Pas, Damien; Da Silva, Anne-Christine (Frontiers in Earth Science, 2024)
The type-Silurian Cellon section in the Carnic Alps in Austria underpins much of the current Silurian conodont zonations, forming the basis for the Silurian timescale. However, the Silurian record of the Cellon section lacks radiometric and astrochronological age constraints, making it difficult to gain insights into the processes pacing Silurian (anoxic) events. To attain age constraints and investigate the pacing Silurian (anoxic) events by astronomical cycles, a cyclostratigraphic study was conducted on high-resolution pXRF (CaO, Al2O3, and Fe2O3) and induration records spanning the Ludlow and Pridoli parts of the Cellon section. Astronomical cycles ranging from precession to the 405-kyr eccentricity cycle were first recognised visually in the field and in proxy records. The visual detection of astronomical cycles served as an input for the WaverideR R package, enabling the tracking of the 405-kyr eccentricity period in each proxy's Continuous Wavelet Transformation (CWT) scalograms. These tracked period curves were combined with external age controls through multiple Monte Carlo simulations, generating an (absolute) age model. This age model is used to assign ages and durations and their respective uncertainties to a hiatus in the Ludfordian, conodont zones, lithological units, geochronological units and events, yielding new ages for Silurian stage boundaries (e.g., Gorstian-Ludfordian boundary at 425.92 ± 0.65 Ma, the Ludfordian-Pridoli boundary at 423.03 ± 0.53 Ma, the Silurian-Devonian boundary at 418.86 ± 1.02 Ma), and new durations for the Ludfordian at 2.89 ± 0.35 Myr and Pridoli at 4.24 ± 0.46 Myr. Furthermore, the imprint of astronomical cycles in the Cellon section itself indicates that the Linde, Klev and Silurian-Devonian boundary events all occur after a 2.4-Myr eccentricity node, indicating pacing by astronomical forcing, similar to other Devonian and Cretaceous anoxic events. The Lau event, however, does not appear to coincide with a 2.4-Myr eccentricity node.